2009
DOI: 10.1159/000235961
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot, Randomized, Double-Blind, Cross-Over Study of High Cut-Off versus High-Flux Dialysis Membranes

Abstract: Background: High cut-off (HCO) membranes may increase β2-microglobulin (β2M) removal compared to standard high-flux membranes.Methods:Eight stable haemodialysis patients were enrolled in a prospective, randomized, double-blind, cross-over study and treated with HCO and high-flux membranes for 2 weeks each, between a 1-week washout period. Primary end point was serum β2M removal. Secondary end points included serum albumin concentrations, albumin and small solute clearances. Results: HCO membranes ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 43 publications
3
24
0
2
Order By: Relevance
“…While some decreases in plasma cytokine levels were even reported after only 4 hours of treatment, the albumin loss was limited and plasma albumin concentrations remained stable. Conversely, Lee and colleagues [76] recently highlighted reductions in serum albumin levels after HCO hemodialysis sessions, leaving this question open to further clinical investigation. To address this issue, membrane parameters and aspects other than the type of modality (diffusion versus convection) - for example, membrane homogeneity in terms of pore size, membrane surface, the use of super-high-flux hemofilters that have a slightly lower cutoff, and the use of the association HVHF-high permeability - certainly need to be taken into account [69].…”
Section: High-adsorption Hemofiltration and High-cutoff Membranesmentioning
confidence: 99%
“…While some decreases in plasma cytokine levels were even reported after only 4 hours of treatment, the albumin loss was limited and plasma albumin concentrations remained stable. Conversely, Lee and colleagues [76] recently highlighted reductions in serum albumin levels after HCO hemodialysis sessions, leaving this question open to further clinical investigation. To address this issue, membrane parameters and aspects other than the type of modality (diffusion versus convection) - for example, membrane homogeneity in terms of pore size, membrane surface, the use of super-high-flux hemofilters that have a slightly lower cutoff, and the use of the association HVHF-high permeability - certainly need to be taken into account [69].…”
Section: High-adsorption Hemofiltration and High-cutoff Membranesmentioning
confidence: 99%
“…Bakulev NSPCCS in 2009-2016, showed the safety and efficacy of the combined therapies mentioned above. [53,54] We observed that the combination of LPS-adsorption and HDF filters with high cut-off EMiC2 membranes led to a 34% MAP increase [from 76 (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81) to 90 (85-102) mmHg, P < 0.001] with reduced vasopressor and inotropic support. The increase in MAP during LPS-adsorption with CPFA was 12% with the significant decrease in vasopressor support [the dose of noradrenaline was halved from 0.2 (0.15-0.3) to 0.1 (0.05-0.15) µg/kg/min, P = 0.024].…”
Section: Extracorporeal Blood Purification In Complex Intensive Theramentioning
confidence: 87%
“…The permeability of these filters is similar to that of the kidney glomerular basement membrane, suggesting that the therapeutic effect of HDF is more physiological. [66,[71][72][73] Several studies have demonstrated the beneficial effect of selective LPS-adsorption, HD/HDF (with high cut-off membranes) and CPFA in sepsis. [58,[64][65][66] We proposed two new techniques of combined blood purification methods in single circuit: (1) LPS-adsorption + HDF using filters with high cutoff membranes; and (2) LPS-adsorption + CPFA.…”
Section: Extracorporeal Blood Purification In Complex Intensive Theramentioning
confidence: 99%
“…However, most patients can stand such degree of albumin loss in a short-term period, or with corresponding quantity of albumin supplementation. Additionally, the reverse osmosis of endotoxin or reverse ultrafiltration from dialysis solution could be increased due to the 2-3 times larger membrane aperture of HCO as compared with high-flux membrane [15,17] . The clearance of uremic toxin increases, while the loss of albumin has become a major obstacle for both PLMs and HCO in clinical application.…”
Section: Protein-leaking Membranes or High Cut-off Membranesmentioning
confidence: 99%